Trend analysis in all-India marine products export using statistical modelling techniques - Venugopalan, R; ., Prajneshu (Indian Journal of Fisheries, 2011)
Various statistical modelling techniques, viz. Polynomial function fittingapproach, Non-linear mechanistic growth modelling approach and ARIMAtime-series methodology are employed for describing the all-India marineproducts export during 1960-'61 to 1994-'95. The underlying assumptions areexamined by statistically sound procedures. Attempts are made to develop themost suitable statistical model. The identified model is then used to forecastthe marine products export for three more years